Prediction of permeability from well logs using a new hybrid machine learning algorithm - Morteza Matinkia; Romina Hashami; Mohammad Mehrad; Mohammad Reza Hajsaeedi; Arian Velayati (Petroleum, 2023)
Permeability is a measure of fluid transmissibility in the rock and is a crucial concept in the evaluation of formations and the production of hydrocarbon from the reservoirs. Various techniques such as intelligent methods have been introduced to estimate the permeability from other petrophysical features. The efficiency and convergence issues associated with artificial neural networks have motivated researchers to use hybrid techniques for the optimization of the networks, where the artificial neural network is combined with heuristic algorithms.This research combines social ski-driver (SSD) algorithm with the multilayer perception (MLP) neural network and presents a new hybrid algorithm to predict the value of rock permeability. The performance of this novel technique is compared with two previously used hybrid methods (genetic algorithm-MLP and particle swarm optimization-MLP) to examine the effectiveness of these hybrid methods in predicting the permeability of the rock.The results indicate that the hybrid models can predict rock permeability with excellent accuracy. MLP-SSD method yields the highest coefficient of determination (0.9928) among all other methods in predicting the permeability values of the test data set, followed by MLP-PSO and MLP-GA, respectively. However, the MLP-GA converged faster than the other two methods and is computationally less expensive.